2021
DOI: 10.1097/iae.0000000000002982
|View full text |Cite
|
Sign up to set email alerts
|

Using Microperimetry and Low-Luminance Visual Acuity to Detect the Onset of Late Age-Related Macular Degeneration

Abstract: To evaluate the performance of microperimetry and low-luminance visual acuity for detecting late age-related macular degeneration (AMD) onset.Methods: Two hundred ninety-two individuals with bilateral large drusen in the Laser Intervention in the Early Stages of AMD study underwent best-corrected visual acuity, lowluminance visual acuity, and microperimetry testing as well as multimodal imaging to detect late (neovascular or atrophic) AMD onset. The performance of the change in the measurement from baseline of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
(55 reference statements)
1
4
0
Order By: Relevance
“…Recent evidence has shown that microperimetric sensitivity and low luminance deficits are poor predictors for AMD progression by themselves when analyzing patients with large drusen, especially when comparing these findings with the presence of pigmentary on fundoscopy. 63 , 64 This may be consistent with making a distinction between growth and regression as two different parts of the drusen life-cycle. Pigmentary changes seen on fundus examination may result from profound RPE–basal lamina alterations, with a loss of overlying photoreceptor bands and associated hypertransmission on OCT B-scans, 46 possibly coexisting with some degree of fading or regression of drusen elements.…”
Section: Discussionsupporting
confidence: 67%
“…Recent evidence has shown that microperimetric sensitivity and low luminance deficits are poor predictors for AMD progression by themselves when analyzing patients with large drusen, especially when comparing these findings with the presence of pigmentary on fundoscopy. 63 , 64 This may be consistent with making a distinction between growth and regression as two different parts of the drusen life-cycle. Pigmentary changes seen on fundus examination may result from profound RPE–basal lamina alterations, with a loss of overlying photoreceptor bands and associated hypertransmission on OCT B-scans, 46 possibly coexisting with some degree of fading or regression of drusen elements.…”
Section: Discussionsupporting
confidence: 67%
“…Individuals in the LEAD Study underwent microperimetry using a standard central 6° radius grid centered on the fovea (based on the preferred retinal locus determined at the start of the examination), consisting of 37 points located at 0°, 1°, 2.33°, 4° and 6° from the fovea. 22 , 23 This stimulus grid is shown in Figure 1 , and all participants performed 2 tests in each eye at every visit. Individuals in the prospective observational study underwent high-density targeted microperimetry testing with an isotropic stimulus pattern also consisting of 37 points that sampled a 1.75° radius (or approximately 1000 μm diameter) region, with an interstimulus spacing of 0.5°.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with controls, patients with iAMD have significant deficits in LLVA ( p < 0.05) [ 101 ]. Nevertheless, research examining LLVA along with microperimetry in the same cohort has suggested that LLVA has limited sensitivity for detecting progression to late AMD [ 105 , 106 ].…”
Section: Structural Biomarkersmentioning
confidence: 99%